Control judicial de constitucionalidad : una crítica de J. Waldron y una defensa de C. Nino - Poznansky, Santiago (2019)
Abstract: I will defend the following claim: if Jeremy Waldron's majoritarian liberalism (detractor of judicial review) wishes to remain committed to its liberal assumptions of what a democracy is, he must admit at least one exception respecting to when constitutional control must be judicialized. That exception is regarding personal autonomy, and I will deal with the case of autonomy linked to the free exercise of the political right to vote. I sketch a mental experiment to show a counterintuitive consequence of Waldronian democracy and its assumptions about fundamental individual rights. I will finish by exposing one of the most finished positions regarding the admission of judicial review in democracy, which is the position of the Argentine liberal Carlos Nino. The novelty of this article is in pointing out the relevance and validity of Nino's democratic thought after more than twenty-five years of the publication of "The constitution of deliberative democracy". I claim that the ninean argument will be the tool that the majoritarians must adopt to resolve the tension between majoritarianism and the moral precommitments of democracy